A newly isolated bacteriophage vB8388 and its synergistic effect with aminoglycosides against multi-drug resistant Klebsiella oxytoca strain FK-8388. (January 2023) - Zhao, Yining; Feng, Luozhu; Zhou, Beibei; Zhang, Xiaodong; Yao, Zhuocheng; Wang, Lingbo; Wang, Zhongyong; Zhou, Tieli; Chen, Lijiang
Abstract: The bacteriophage vB8388 can lyse multi-drug resistant Klebsiella oxytoca strain FK-8388 and maintain stability in a wide range of temperatures (from 4 °C to 80 °C) and pHs (3–11). Bioinformatics analysis showed that vB8388 is a linear double-stranded DNA virus that is 39, 750 long with 50.65% G + C content and 44 putative open reading frames (ORFs). Phage vB8388 belongs to the family Autographviridae and possesses a non-contractile tail. The latency period of vB8388 was approximately 20 min. The combination of phage vB8388 and gentamicin, amikacin, or tobramycin could effectively inhibit the growth of K. oxytoca strain FK-8388, with a decrease of more than 4 log units within 12 h in vitro . Phage vB8388 showed a strong synergistic effect with gentamicin that could enhance the anti-biofilm effect of vB8388. The phage + gentamicin combination also showed synergy in vivo in the larval infection model of Galleria mellonella . In conclusion, the findings of this study suggest the potential of phage + antibiotic combination therapy to be used as an alternative therapeutic approach for treating infectious diseases caused by multidrug-resistant bacteria. Highlights: A lytic bacteriophage against a multidrug-resistant Klebsiella oxytoca strain. Synergistic effect between bacteriophage and aminoglycosides in vitro. The mature biofilm of K. oxytoca was significantly eradicated in the phage + gentamicin combination treatment groups. Gentamicin and amikacin showed synergistic effects with phage in vivo.